2020
DOI: 10.1111/tri.13682
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of kidney transplant by using restored kidney grafts after tumour ex vivo excision – a prospective study

Abstract: The aim of this study is to report long-term outcomes of kidney transplantation by using the kidney graft after a small tumour ex vivo excision. A structured programme was established to use the restored kidney graft from urological referral after radical nephrectomy. The criteria were defined as tumour size ≤3 cm, margin clear on frozen section and recipients aged ≥60 years or those on the urgent list for transplantation as a result of imminent lack of dialysis access. The recipients were followed up regularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Donor and recipients were followed for up to 135 months post-transplant without RCC recurrence. He et al ( 31 ) also report on their experience with 28 recipients that received a PN kidney graft transplant from living unrelated donors, showing no recurrence of malignancy at a median of 7.5 years of follow up. Regarding living donors with renal cysts, Grotemeyer et al ( 32 ) published a retrospective review of 268 living donor kidney transplants where 25 kidneys were found to have cysts.…”
Section: Discussionmentioning
confidence: 98%
“…Donor and recipients were followed for up to 135 months post-transplant without RCC recurrence. He et al ( 31 ) also report on their experience with 28 recipients that received a PN kidney graft transplant from living unrelated donors, showing no recurrence of malignancy at a median of 7.5 years of follow up. Regarding living donors with renal cysts, Grotemeyer et al ( 32 ) published a retrospective review of 268 living donor kidney transplants where 25 kidneys were found to have cysts.…”
Section: Discussionmentioning
confidence: 98%
“…He et al’s prospective study followed 28 KTRs whose donors received a radical nephrectomy to remove small tumors (≤3 cm) prior to transplant. Only 7% of KTRs experienced allograft rejection and a median of 7.5 years of follow-up revealed no tumor reoccurrence [ 62 ]. The study supports the notion that the risk of transmitting RCC to the recipient is minimal given pre-transplant resection.…”
Section: Rcc Outcomes In Eskd and Transplantationmentioning
confidence: 99%
“…The latter has been pioneered by Australian transplant centers, and a recent report summarize that among 107 such transplantations, only 2 recurrences (1.87%) were seen after a median of 7 y of follow-up, making a strong argument for the low oncological risk. 69 However, most patients with a small RCC require only partial nephrectomy, ruling out donation. 70 Details of surgical technique and monitoring are reviewed elsewhere.…”
Section: Reveiwmentioning
confidence: 99%